PENGARUH SUDUT KERAT DAN BAGIAN BATANG TERHADAP SIFAT PENGGERGAJIAN KAYU KELAPA (Cocos nucifera. L.) - Osly Rachman (Jurnal Penelitian Hasil Hutan, 1986)
Eighteen green cocowood samples, 3 m in length each were sawn into 3 cm thick boards. Trunk samples consisted of two groups, butt logs and top logs. Each group was sawn with 3 degrees of hook angle, namely 19,22 and 25 degrees. Sawing properties, i.e., power consumption, sawing productivity and lumber recovery were related with hook angle and trunk portion. The results reveal that trunk portion and hook angle had a significant effect on power consumption. The butt logs consumed power higher than top logs. Trunk portion had no effect on sawing productivity but greater hook angle tends to increase the productivity. Hook angle and trunk portion had no effect on recovery.